(untitled) (Castilla. Estudios de Literatura, 2016)
In this paper I will provide a segmentation proposal for Viuda, casada y doncella, a play by Lope de Vega. Not only will I take the usual aspects into account (empty stages, versification, space, time), but also mechanisms such as its performance on stage and its reception by the audience in the Golden Age. I will also try to show a metrical peculiarity from Viuda, casada y doncella that, in my opinion, makes it incomparable with other cases analyzed by critics. Finally, I will present the following hypothesis: Lope may have used a metrical outline in order to write this comedia.